(untitled) (The Review of Diabetic Studies, 2025)
Background: Osteoarthritis (OA) and other degenerative joint diseases are leading causes of global disability, with traditional management strategies often failing to alter disease progression. This systematic review evaluates the efficacy and safety of innovative approaches, including biological therapies, pharmacological agents, and digital health interventions, for managing these conditions. Methods: A comprehensive search was conducted across multiple electronic databases (PubMed, Scopus, Web of Science, Google Scholar) for studies published up to 2025. Included were clinical trials and systematic reviews evaluating innovative interventions for OA, reporting patient-centered outcomes such as pain, function, or disease modification. Data were extracted and synthesized narratively due to heterogeneity among studies. Methodological quality was assessed using appropriate tools such as the Cochrane Risk of Bias tool. Results: Eleven studies met the inclusion criteria. Biological interventions like platelet-rich plasma (PRP) and umbilical cord-derived mesenchymal stem cells (UC-MSCs) showed promise for long-term symptom improvement and potential disease modification, with PRP demonstrating superiority over corticosteroids at one-year follow-up. The nerve growth factor inhibitor tanezumab provided rapid pain relief but was associated with safety risks, including rapidly progressive osteoarthritis. Digital health tools, including mobile apps and telerehabilitation, were found to be feasible, acceptable, and non-inferior to in-person care for improving pain and function. Conclusion: Innovative approaches in OA management—including biologics, novel pharmaceuticals, and digital health strategies—offer significant potential beyond conventional care. A multimodal, personalized treatment model integrating these innovations is recommended to improve patient outcomes, balancing efficacy with safety. Future research should focus on large-scale randomized controlled trials with standardized protocols to confirm long-term benefits and safety profiles.